MIKROZONASI SEISMIK UNTUK RENCANA TATA RUANG DAN WILAYAH DI KOTAAGUNG, LAMPUNG - ANGGRAENI, ERWINDA FENTY ([Yogyakarta] : Universitas Gadjah Mada, 2015)
A measurement of single sensor microtremor and arrays microtremor has been done in Kotaagung, which is located at the Sumatera active faults. The main purpose of this study is to determine and to map the distribution of predominant frequency f0, amplification A0, seismic vulnerability index Kg, peak ground acceleration (PGA) α, ground shear strain γ, Vs30_array, sedimentary layer thickness h and shear wave velocity vs as well as to analyze the relationship between seismic vulnerability index with the urban planning in Kotaagung. Data have been analyzed using method of Horizontal to Vertical Spectral Ratio (HVSR), Spatial Auto-Correlation (SPAC) and Simple Additive Weight (SAW). The results show that the predominant frequency varies from 0,343 to 11,141 Hz; amplification varies from 0,962 to 7,994; seismic vulnerability index varies from 0,149 to 75,616; PGA surface layer varies from 155 to 1033 gal; PGA bedrock varies from 175 to 212 gal; Vs30 at locations C1, C2, C3 and C4 respectively 404,10 m/s, 222,13 m/s, 326,73 m/s and 301,25 m/s; ground shear strain varies from 3,08 x 10-5 to 1,46 x 10-2, sedimentary layer thickness varies from 3,38 to 424,30 m; and vs varies from 150,7 to 581,76 m/s. Therefore, the seismic microzonation for urban planning in Kotaagung identified has a very low seismic vulnerability index (risk category I, II, III and IV), low (risk category I, II, III and IV), and medium to very high (risk category I). Subdistrict of West Kotaagung identified has a very low and low seismic vulnerability index. Subdistrict Kotaagung has a very low, low, medium and very high seismic vulnerability index. Subdistrict of East Kotaagung has a very low, low, medium and very high seismic vulnerability index.